2021
DOI: 10.1111/hdi.12999
|View full text |Cite
|
Sign up to set email alerts
|

Postdialysis serum phosphate equilibrium in hemodialysis patients on a controlled diet and no binders

Abstract: Background: Studies evaluating the change in serum phosphate post hemodialysis (HD) demonstrate an initial decline during dialysis but a rebound post dialysis. However, previous studies were done on usual diet and phosphate binders, with limited number of blood draws, confounding conclusions. We determined serum phosphate reduction, rebound, and equilibrium over 48 h in HD patients consuming a controlled, low phosphorus diet without binders.Methods: Serum phosphate (mg/dL) was analyzed before and after a HD tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The current belief that phosphate returns to the basal level a few hours after dialysis was not confirmed in a recent study of haemodialysis patients on a low-phosphate diet with no binders [39]. In that study, phosphate returned to basal levels within the first 24 h after dialysis in less than 40% of the individuals.…”
Section: Phosphate Balance In Dialysismentioning
confidence: 85%
See 1 more Smart Citation
“…The current belief that phosphate returns to the basal level a few hours after dialysis was not confirmed in a recent study of haemodialysis patients on a low-phosphate diet with no binders [39]. In that study, phosphate returned to basal levels within the first 24 h after dialysis in less than 40% of the individuals.…”
Section: Phosphate Balance In Dialysismentioning
confidence: 85%
“…An evaluation of 455 dialysis sessions showed that at least 38 h of dialysis weekly are required to maintain normal phosphate levels in patients with a phosphate intake of 0.7 g/ day not treated with binders [37]. The predialysis serum phosphate concentration also influences phosphate removal [38], and restricting dietary phosphate may blunt postdialysis rebound [39]. Hemodiafiltration has been shown to remove higher amounts of phosphate in patients with predialysis levels below 7 mg/dl [40].…”
Section: Phosphate Balance In Dialysismentioning
confidence: 99%
“… 33 Recent investigation of the rebound increment of serum P after HD revealed that the low serum P levels increased slightly just after the session, and remained plateaued at this level for the following 3 to 4 hours, with no additional increase. 47 Although it is not clear to what extent this transient hypophosphatemia affects QT interval through adenosine triphosphate deficiency in the myocardium, it is clear that fatal arrhythmias often occur within 12 hours after an HD session. 48 We believe that hypophosphatemia after HD could be responsible for the present results.…”
Section: Discussionmentioning
confidence: 99%